Expression profiling suggests the involvement of hormone-related, metabolic, and Wnt signaling pathways in pterygium progression - Li, Jiarui; Tao, Tianchang; Yu, Yingying; Xu, Ningda; Du, Wei; Zhao, Mingwei; Jiang, Zhengxuan; Huang, Lvzhen (Frontiers in Endocrinology, 2022)
Background Pterygium is an ocular surface disease that can cause visual impairment if it progressively invades the cornea. Although many pieces of research showed ultraviolet radiation is a trigger of pterygium pathological progress, the underlying mechanism in pterygium remains indistinct. Methods In this study, we used microarray to evaluate the changes of transcripts between primary pterygium and adjacent normal conjunctiva samples in China. Then, we performed Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses. Moreover, we constructed protein-protein interaction (PPI) and miRNA-mRNA regulatory networks to predict possible regulatory relationships. We next performed gene set enrichment analysis (GSEA) to explore the similarities and differences of transcripts between Asian studies from the Gene Expression Omnibus database. Furthermore, we took the intersection of differentially expressed genes (DEGs) with other data and identified hub genes of the development of pterygium. Finally, we utilized real-time quantitative PCR to verify the expression levels of candidate genes. Results A total of 49 DEGs were identified. The enrichment analyses of DEGs showed that pathways such as the Wnt-signaling pathway and metabolism-related pathways were upregulated, while pathways such as hormone-related and transcription factor-associated pathways were downregulated. The PPI and miRNA-mRNA regulatory networks provide ideas for future research directions. The GSEA of selecting Asian data revealed that epithelial-mesenchymal transition and myogenesis existed in the pathology of pterygium in the Asian group. Furthermore, five gene sets (interferon-gamma response, Wnt beta-catenin signaling, oxidative phosphorylation, DNA repair, and MYC targets v2) were found only in our Chinese datasets. After taking an intersection between selecting datasets, we identified two upregulated (SPP1 and MYH11) and five downregulated (ATF3, FOS, EGR1, FOSB, and NR4A2) hub genes. We finally chose night genes to verify their expression levels, including the other two genes (SFRP2 and SFRP4) involved in Wnt signaling; Their expression levels were significantly different between pterygium and conjunctiva. Conclusions We consider hormone-related, metabolic, and Wnt signaling pathways may be important in the pathology of pterygium development. Nine candidate genes we identified deserve further study and can be potential therapeutic targets.